A conceptual framework: determinants of food waste behavioral intention among millennials in the food and beverage industry / Nadzirah Maripat, Rasidah Hamid and Nur'hidayah Che Ahmat - Maripat, Nadzirah; Hamid, Rasidah; Che Ahmat, Nur'hidayah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Food waste's financial and environmental costs challenge the food and beverage industry. The critical driver of food waste is often aimed at Millennial consumers. This attracts the interest of researchers to determine Millennials’ consumer behaviour intention towards the issue of food waste. However, the Millennials need the motivation of behavioural intention towards food waste. This article aims to build a model by proposing a new conceptual framework consisting of consumer value with two dimensions: environmental concern and materialism value, self-efficacy, and food waste behavioral intention among Millennials to understand better the consumer food waste issues in the food and beverage industry. As a result, this finding will provide knowledge through the food and beverage industry by examining the variables that lead to the food waste behavioural intention among Millennial consumers.